Knowledge Production, Multifunctionality Of Agriculture And Public Decisions: Critical Issues Of Contemporary Controversies - Laurent, Catherine E; Labarthe, Pierre; Berriet-Solliec, Marielle; Trouve, Aurelie; Kirsch, Marc (IDEAS Working Paper Series from RePEc, 2009)
Various theoretical models of public policy analysis are used to treat situations of decision-making in which public deciders have to take into account the multifunctionality of agriculture. For some, science-society relations are not really problematical. Others acknowledge the current attempts of these policy-makers to find adequate scientific knowledge, and the difficulties they encounter. These difficulties stem partly from the very content of knowledge produced by research. Could other modes of production be more efficient? The status of the knowledge produced by these approaches is a subject of debate. Bridging the divide between science and policy more effectively is not only a question of knowledge brokerage. Accessibility and reliability of the existing evidences are also problems to be addressed. The debates around evidence-based practices may provide some landmarks in this new situation although they also emphasize the limits of the tools that can be built for this purpose.